2011
DOI: 10.2337/dc10-1076
|View full text |Cite
|
Sign up to set email alerts
|

Liver ATP Synthesis Is Lower and Relates to Insulin Sensitivity in Patients With Type 2 Diabetes

Abstract: OBJECTIVESteatosis associates with insulin resistance and may even predict type 2 diabetes and cardiovascular complications. Because muscular insulin resistance relates to myocellular fat deposition and disturbed energy metabolism, we hypothesized that reduced hepatic ATP turnover (fATP) underlies insulin resistance and elevated hepatocellular lipid (HCL) contents.RESEARCH DESIGN AND METHODSWe measured hepatic fATP using 31P magnetic resonance spectroscopy in patients with type 2 diabetes and age- and body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
147
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(168 citation statements)
references
References 24 publications
(48 reference statements)
13
147
3
Order By: Relevance
“…Moreover, although we cannot completely rule out the possibility that some SNPs in or near OxPhos genes may contribute to impaired glucose-stimulated insulin secretion, our results provide evidence that the major role played by insulin resistance in the pathogenesis of type 2 diabetes cannot be explained by such genetic variants. The hypothesis of a potential association between common variation in OxPhos genes and type 2 diabetes was strongly supported a priori by numerous metabolic and physiological studies [7][8][9][10][11][12][13][14][15][16][17][18]. This makes our study unique compared with replication studies and meta-analysis of previously identified type 2 diabetes risk alleles, for most of which knowledge of the underlying phenotype leading to type 2 diabetes is limited [23].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Moreover, although we cannot completely rule out the possibility that some SNPs in or near OxPhos genes may contribute to impaired glucose-stimulated insulin secretion, our results provide evidence that the major role played by insulin resistance in the pathogenesis of type 2 diabetes cannot be explained by such genetic variants. The hypothesis of a potential association between common variation in OxPhos genes and type 2 diabetes was strongly supported a priori by numerous metabolic and physiological studies [7][8][9][10][11][12][13][14][15][16][17][18]. This makes our study unique compared with replication studies and meta-analysis of previously identified type 2 diabetes risk alleles, for most of which knowledge of the underlying phenotype leading to type 2 diabetes is limited [23].…”
Section: Discussionmentioning
confidence: 54%
“…Based on the substantial evidence that mitochondrial dysfunction is linked to insulin resistance and beta cell dysfunction, and is present in multiple tissues relevant to the pathogenesis of type 2 diabetes [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], we hypothesised that common variation in OxPhos genes contributes to an increased risk of type 2 diabetes or influences metabolic traits related to the disease. OxPhos gene variants showing nominal association with type 2 diabetes in a meta-analysis of three GWA studies that were part of the DIAGRAM Study [28] were selected for follow-up in an independent cohort of Danish individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this contention, lower liver ATP levels (21), fATP (6), and ATP recovery upon fructose challenge (24) provide evidence for lower hepatic mitochondrial function, at least in insulin-resistant groups such as severe obesity or type 2 diabetes. Furthermore, impaired hepatic energy metabolism could subsequently raise plasma FFA via lipolysis of VLDL (3) and in turn induce lipid-mediated muscle insulin resistance (25).…”
Section: Resultsmentioning
confidence: 94%
“…Increased insulinstimulated de novo hepatic lipogenesis after carbohydrate intake might represent an important sink for excess glucose, ultimately improving glucose homeostasis. On the other hand, steatosis may result from inadequate hepatic oxidation rates (6), subsequently leading to increased lipid flux to skeletal muscle. Indeed, insulin resistance frequently associates with accumulation of IMCL or lipid metabolites (3).…”
mentioning
confidence: 99%